Case Report: The Complete Remission of a Mixed Germ Cell Tumor With Somatic Type Malignancy of Sarcoma Type With a GCT-Oriented Therapy: Clinical Findings and Genomic Profiling - Pantaleo, Maria A.; Mandruzzato, Marcella; Indio, Valentina; Urbini, Milena; Nannini, Margherita; Gatto, Lidia; Schipani, Angela; Fiorentino, Michelangelo; Franceschini, Tania; Ambrosini, Valentina; Di Scioscio, Valerio; Saponara, Maristella; et al. (Frontiers in Oncology, 2021)
Somatic malignant transformation in a germ cell tumor (GCT) is the development of non-germ malignancies; much of available literature refers to teratoma with malignant transformation (TMT). There are various transformation histologies such as sarcoma, adenocarcinoma, primitive neuroectodermal tumors, and more rarely carcinoid tumors, hemangioendothelioma, lymphoma, or nephroblastoma. The treatments of these entities include surgery and/or chemotherapy. A standard approach in choosing chemotherapy in TMT cases has not yet been established. Many authors suggested using chemotherapeutic agents based on the transformed histology, while others suggested GCT-oriented therapy combined with surgery as the primary treatment, reserving histology-driven chemotherapies for metastatic relapse. We report the clinical findings and the genomic profile of a mixed GCT case with somatic-type malignancy of sarcoma type. We achieved a complete radiological response with GCT-oriented chemotherapy performed as salvage therapy after sarcoma-histology therapy. In addition, molecular profiles with RNA-sequencing and exome sequencing analyses of the primary tumor and the tumor with somatic-type malignancy of sarcoma type were explored.